Urban Drainage Capacity On Jln. East Perjuangan, Medan Perjuangan District - Monaqia Pricilia Br Sitanggang; Farezi Ripantri; Yuni Yolanda (CV. SINAR HOWUHOWU, 2026)
This research was motivated by the problem of inundation and flooding on Jalan Perjuangan, Medan Perjuangan District, which was caused by the drainage system capacity not being optimal. The aim of this research is to evaluate the capacity and performance of drainage channels based on existing dimensions and assess the channel's ability to accommodate the planned discharge at various return periods. The methods used include hydrological and hydraulic analysis. Hydrological analysis is carried out through rainfall distribution tests, Chi-Square tests, and determining planned rainfall with various return periods. Rain intensity is calculated using the Mononobe method. Next, hydraulic analysis is carried out using the Manning formula to determine the flow capacity of the drainage channel. The data used in this research consists of primary data from field surveys and secondary data from related agencies. The research results show that the most suitable rainfall distribution is Log Pearson Type III. The existing channel dimensions of 4 m × 3 m have proven capable of accommodating the planned discharge up to a return period of 100 years with a discharge of 54 m³/sec, so that technically it still meets the currently required capacity. However, factors such as increasing population, sediment accumulation and domestic waste disposal have the potential to reduce channel performance in the future. Therefore, routine maintenance efforts and sustainable drainage management planning are needed to ensure the system continues to function optimally and is able to anticipate increases in flow loads in the future.